2017
DOI: 10.3847/2041-8213/aa9e0a
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism for the Energy Buildup Driving Solar Eruptive Events

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…However, the newly emerged bipoles do not erupt immediately, which indicates that they emerge with insufficient free energy to enable eruption. Therefore, we conclude that shearing and/or rotational photospheric motions are the most likely sources of the energy buildup that forms the filament channel and is released through eruption (e.g., Wyper et al 2018b), as in the helicity condensation model (Antiochos 2013;Knizhnik et al 2017;Dahlin et al 2018). Some of the larger analyzed events clearly exhibit rotational and/or shearing displacements between the minority polarity and its surroundings (e.g., see animations of Figs.…”
Section: Discussionmentioning
confidence: 78%
“…However, the newly emerged bipoles do not erupt immediately, which indicates that they emerge with insufficient free energy to enable eruption. Therefore, we conclude that shearing and/or rotational photospheric motions are the most likely sources of the energy buildup that forms the filament channel and is released through eruption (e.g., Wyper et al 2018b), as in the helicity condensation model (Antiochos 2013;Knizhnik et al 2017;Dahlin et al 2018). Some of the larger analyzed events clearly exhibit rotational and/or shearing displacements between the minority polarity and its surroundings (e.g., see animations of Figs.…”
Section: Discussionmentioning
confidence: 78%
“…High-resolution numerical simulations (Knizhnik et al 2015(Knizhnik et al , 2017aZhao et al 2015) have confirmed the accumulation of helicity at the perimeter of a compact region of such vortical flows in a plane-parallel corona, supporting the validity of the three-stage process described above. In a more definitive study of helicity condensation, in a bipolar magnetic region with a true PIL at the solar surface, Knizhnik et al (2017b) formed a filament channel having concentrated shear and dipped field lines, as observed on the Sun.…”
Section: Introductionmentioning
confidence: 81%
“…Taylor's hypothesis has been largely verified in laboratory devices, such as reverse field pinches, where conducting walls with B · n| S = 0 isolate the plasma (Butt et al 1976). Furthermore, helicity conservation has been observed in numerous MHD simulations with high Lundquist number (e.g., MacNeice et al 2004;Knizhnik et al 2017). The magnetic helicity H is also a robust invariant in periodic geometries in the absence of a mean magnetic field.…”
Section: Magnetic Helicitymentioning
confidence: 95%